An open source solution to a common collection problem: the Africa image and map portal. Issue 4 (3rd June 2019) - Partlow, Mia; Quill, Theresa; Djenno, Mireille
Abstract : Purpose: The purpose of this paper is to provide an overview of the Africa image and map portal (AIMP) project's origins and development, along with its applications to date. This paper includes methods and a step-by-step appendix so that the project can be reproduced at other institutions. Design/methodology/approach: AIMP was created with a suite of free and open source software, including QGIS, Mapbox.js and GitHub. Built around the concept of an interactive index map, AIMP allows for geographic searching of maps, posters and images from Indiana University's (IU) African Studies collections. This paper presents a case study for the use of this geographic discovery tool at an academic library. Findings: AIMP has allowed comparison of collection strengths with research interests of IU African Studies affiliates and to make strategic collection development decisions that will best serve the authors' patrons. The instruction applications of AIMP are also full of potential. To date, the Librarian for African Studies has used the portal to familiarize faculty, as well as undergraduate and graduate students, with the range of image and map resources available to them, in a variety of settings. Social implications: AIMP allows researchers around the world to discover materials through a geographic search, dramatically connecting and increasing access to and discoverability of these important collections. The use of free and open source geospatial software (foss4g) means that the interface does not rely on an institution's proprietary software-licensing agreements, making it replicable for other institutions. This use of foss4g widens access to maps, spatial data, images and posters of Africa held by IUL to a global audience. Originality/value: While interactive index maps are popular among map libraries, AIMP uniquely acts as a discovery portal for a variety of media, including images and posters. In this way, AIMP works to overcome institutional silos and increase discoverability of these important collections to a global audience.